The 10th International Conference on Digital Technologies 2014 2014
DOI: 10.1109/dt.2014.6868733
|View full text |Cite
|
Sign up to set email alerts
|

BioImage Informatics: The challenge of knowledge extraction from biological images

Abstract: Bioimage Informatics is a rapidly growing research field that is giving fundamental contributions to research in biology and biomedicine aiming at facilitating the extraction of quantitative information from images. Great advances in biological tissue labeling and microscopic imaging are radically changing how biologists visualize and study the molecular and cellular structures. These devices nowadays produce terabytesized multi-dimensional images: how to automatically and efficiently extract objective knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In neuroscience and developmental biology, the field of computer science is contributing new image processing and analysis workflows, advancing large‐scale brain mapping and analysis of tissue morphodynamics . Implementing similar unbiased strategies for IV‐MPM studies of cancer will allow us to accelerate the pace of discoveries.…”
Section: Towards Multiparametric Iv‐mpm Of Cancer: New Imaging and Immentioning
confidence: 99%
See 1 more Smart Citation
“…In neuroscience and developmental biology, the field of computer science is contributing new image processing and analysis workflows, advancing large‐scale brain mapping and analysis of tissue morphodynamics . Implementing similar unbiased strategies for IV‐MPM studies of cancer will allow us to accelerate the pace of discoveries.…”
Section: Towards Multiparametric Iv‐mpm Of Cancer: New Imaging and Immentioning
confidence: 99%
“…41,42 This work also indicated that tumor cell behavior is a result of complex interactions among cues present in the tumor microenvironment and that machine learning algorithms have the ability to grasp this complexity. 18,43 In neuroscience and developmental biology, the field of computer science is contributing new image processing and analysis workflows, advancing large-scale brain mapping [44][45][46] and analysis of tissue morphodynamics. [47][48][49] Implementing similar unbiased strategies for IV-MPM studies of cancer will allow us to accelerate the pace of discoveries.…”
Section: (Semi)automated Image Processing and Machine Learning Clasmentioning
confidence: 99%